Onus probandi - its functions and conditioning - Szymanek, Krzysztof (Folia Philosophica, 2006)
The subject of analysis constitutes the role of onus probandi in the decisionmaking process, the influence of this rule on the final result of a dispute, as well as the course of argumentative turns determined by various values, such as truth and utility. Some aspects of onus probandi are analysed via formal methods within a simple model, taking into account some aspects of decision-making once the supposition has been confirmed.